A new genus and species of subfamily Dendrothripinae (Thysanoptera: Thripidae) from India - Pal, Shash; Kumar, Vikas; Panjaliya, Rakesh Kumar; Tyagi, Kaomud (Zootaxa, 2022)
Jammuthrips paikulensis gen. et sp. n. is described from Jammu & Kashmir, Union territory of India and the morphological relationships among the closely related genera of subfamily Dendrothripinae are discussed. Key to Indian genera of subfamily Dendrothripinae is provided. Two DNA barcodes of new species were generated and submitted to The Barcode of Life Data Systems (BOLD).